URGENSI PERSONAL BRANDING BAGI PUSTAKAWAN DI ERA PANDEMI - Fransisca Rahayuningsih (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2021)
As a result of the Covid-19 outbreak, libraries must change their habits and order in providing library services. Library services, which were initially carried out in person or on the spot, were turned into online services to facilitate and provide convenience for users and librarians. Librarians are expected to be more creative in creating new innovations in providing online services to users. Librarians must still be able to provide excellent service to users even with various existing limitations, both librarians, infrastructure, and library collections. In the midst of the limitations of excellent service, the librarian is the key to this excellent service. Librarians must have a brand. How the librarian shows brand personality, brand-ability, brand value, and has a stimulus that produces positive perceptions. The brand of personality to build is one that is friendly, cooperative, forgiving, understanding, and good on good terms with other people. Librarians must also hone their brand personality in terms of being systematic, careful, thorough, responsible, and disciplined. Librarians should also have less negative emotionality, so that they are relatively balanced, calm, steadfast, and feel safe. Librarians must be sociable, articulate, assertive, and open to new relationships. besides that the librarian must have a high, to listen to new ideas and change ideas. The brand of librarian abilities that must be built is solving problems systematically, being able to find and finding creative and original ideas, managing people, coordinating with other people or teamwork, regulating and controlling emotions, being able to draw decisions, under any conditions, have a service or service orientation, negotiate, have cognitive flexibility or are able to think spontaneously in response to adjusting to situational needs. The librarian's brand value that must be built is the value of integrity and leadership. In terms of integrity, librarians must value honesty in speaking and acting; be able to balance/be consistent between thoughts, words, and actions; fair in treating others; have a high dedication to the institution; can always be trusted in carrying out the mandate and carrying out daily tasks. In addition to leadership, librarians must build teamwork in order to generate new ideas, ideas, suggestions so that work goals can be implemented.